Role of protein intake in maintaining muscle mass composition among elderly females suffering from sarcopenia - Ishaq, Izwa; Noreen, Sana; Maduabuchi Aja, Patrick; Atoki, Ayomide Victor (Frontiers in Nutrition, 2025)
Dietary protein is crucial in preserving muscle mass and promoting long-term bone health, particularly in aging populations. The novelty of this study lies in evaluating the impact of varying protein intake levels (0.8 vs. 1.2 g/kg b.w/d) on muscle mass composition in elderly females suffering from sarcopenia. For this purpose, in this research trial, a total of 126 participants (60–75 years) were enrolled and equally divided into two groups: normal protein intake (0.8 g/kg b.w/d) and moderately high protein intake (1.2 g/kg b.w/d) for 12 weeks. The effects of dietary protein were assessed using anthropometric measurements, magnetic resonance imaging (MRI), handgrip, and knee flexion tests with baseline and post-intervention comparisons. Statistical analysis was conducted using SPSS, employing paired sample t-test at a significance level of p < 0.05. Results indicated a significant improvement in muscle mass composition with moderately high protein intake. Anthropometric parameters, including body mass (83.51 ± 4.23 kg) and waist circumference (113.90 ± 10.82 cm), showed notable enhancement in the moderately higher protein group. Muscle function and imaging assessments, such as handgrip strength and knee flexion, demonstrated improved functionality. MRI-derived measurements of the muscle composition of the calf (141.23 ± 4.87 MCSA, mm2 × 104) and thigh (258.04 ± 7.26 MCSA, mm2 × 104) further confirmed the positive impact of increased protein intake. The study concluded that a moderately high protein diet effectively supports muscle health in elderly females with sarcopenia. Therefore, an adequate protein intake may serve as a strategic nutritional intervention to mitigate muscle loss and improve overall physical function in aging women.